Museum Genomics Illuminate the High Specificity of a Bioluminescent Symbiosis for a Genus of Reef Fish - Gould, Alison L.; Fritts-Penniman, Allison; Gaisiner, Ana (Frontiers in Ecology and Evolution, 2021)
Symbiotic relationships between bioluminescent bacteria and fishes have evolved multiple times across hundreds of fish taxa, but relatively little is known about the specificity of these associations and how stable they are over host generations. This study describes the degree of specificity of a bioluminescent symbiosis between cardinalfishes in the genus Siphamia and luminous bacteria in the Vibrio family. Primarily using museum specimens, we investigated the codivergence of host and symbiont and test for patterns of divergence that correlate with both biogeography and time. Contrary to expectations, we determined that the light organ symbionts of all 14 Siphamia species examined belong to one genetic clade of Photobacterium mandapamensis (Clade II), indicating that the association is highly specific and conserved throughout the host genus. Thus, we did not find evidence of codivergence among hosts and symbionts. We did observe that symbionts hosted by individuals sampled from colder water regions were more divergent, containing more than three times as many single nucleotide polymorphisms than the rest of the symbionts examined. Overall, our findings indicate that the symbiosis between Siphamia fishes and P. mandapamensis Clade II has been highly conserved across host taxa and over a broad geographic range despite the facultative nature of the bacterial symbiont. We also present a new approach to simultaneously recover genetic information from a bacterial symbiont and its vertebrate host from formalin-fixed specimens, enhancing the utility of museum collections.